2021
DOI: 10.3389/fimmu.2021.613530
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Expression in Cancer Cells and Its Critical Roles in Tumorigenesis

Abstract: Traditionally, immunoglobulin (Ig) was believed to be produced by only B-lineage cells. However, increasing evidence has revealed a high level of Ig expression in cancer cells, and this Ig is named cancer-derived Ig. Further studies have shown that cancer-derived Ig shares identical basic structures with B cell-derived Ig but exhibits several distinct characteristics, including restricted variable region sequences and aberrant glycosylation. In contrast to B cell-derived Ig, which functions as an antibody in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 106 publications
1
61
0
Order By: Relevance
“…This study is the first to demonstrate that all the five classes of Ig heavy chains and two types of Ig light chains could be expressed in non-B cells. IGHG has been reported in various non-B neoplastic cells and has been shown to promote malignant behaviors in cancer cells [ 8 ]. Similarly, we detected a high frequency of IGHG expression in myeloblasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is the first to demonstrate that all the five classes of Ig heavy chains and two types of Ig light chains could be expressed in non-B cells. IGHG has been reported in various non-B neoplastic cells and has been shown to promote malignant behaviors in cancer cells [ 8 ]. Similarly, we detected a high frequency of IGHG expression in myeloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal immunoglobulin (Ig) gene rearrangement has been used as a diagnostic tool for B-cell lymphomas [ 7 ]. Although B-cells and plasma cells have been considered as the only source of Ig, a series of reports from our group and others have demonstrated that Ig could be expressed in many epithelial cancer cells [ 8 ], as well as in normal non-hematopoietic cells [ 9 , 10 , 11 ]. Moreover, other than acting as natural antibodies [ 12 , 13 ], non-B-derived Ig, especially IgG, with unique rearrangement patterns or glycosylation profile, has been shown to play a role in promoting cancer cell survival and proliferation, as well as cancer invasion and metastasis [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, cancer-derived immunoglobulins show potential applications as diagnostic and therapeutic targets for cancer patients. 31 Studies have shown that AML-derived IgG may be related to the occurrence of leukaemia and the progression of AML.…”
Section: Discussionmentioning
confidence: 99%
“…While germline IGH genotypes have generally been overlooked in GWAS and other disease association studies, partially due to genotyping challenges, there is increasing interest in investigating the effect of IGH germline genetic variation on the adaptive immune system and disease[3, 5]. In fact IGHV germline genetic variation has recently been associated with clinical phenotypes including infectious disease and vaccine response [11, 12, 13, 14], autoimmune/inflammatory conditions[15, 16, 17], and cancer[18].…”
Section: Introductionmentioning
confidence: 99%